THE PRECISION OF ROD-ROW TESTS WITH BARLEY GROWN AT THREE TOPOGRAPHICAL LOCATIONS AS INFLUENCED BY ALLEVIATING A PHOSPHORUS DEFICIENCY - Anderson, C. H. (Canadian Journal of Plant Science, 1963)
At Fort Vermilion during 1960 to 1962, inclusive, Olli barley was grown on low, level and high land using four rates of ammonium-phosphate fertilizer. Increasing rates of fertilizer increased the yield of barley. Fertilizer also increased the precision of the tests for yield with maximum precision generally occurring with the 50-pound-per-acre rate. The widest range in coefficients of variation over the 3-year period occurred on high land followed by level land and the least range on low land. With the exception of low land the greatest annual range in precision occurred with the unfertilized plots.